PD‐L1 and PD1 expression in post‐transplantation lymphoproliferative disease (PTLD) of childhood and adolescence: An inter‐ and intra‐individual descriptive study covering the whole spectrum of PTLD categories. (3rd July 2019) - Schiefer, Ana‐Iris; Salzer, Elisabeth; Füreder, Anna; Szepfalusi, Zsolt; Müller‐Sacherer, Thomas; Huber, Wolf‐Dietrich; Michel‐Behnke, Ina; Lawitschka, Anita; Pichler, Herbert; Mann, Georg; Hutter, Caroline; Simonitsch‐Klupp, Ingrid; et al.
Abstract: Therapy of children with post‐transplantation lymphoproliferative disorder (PTLD) after hematopoietic stem cell (HSCT) and solid organ transplantation (SOT) can be challenging. In this retrospective study, we investigated PD‐L1 and PD1 expression in all PTLD categories of childhood and adolescence to see whether checkpoint inhibition with PD‐L1/PD1 inhibitors may serve as a therapy option. We included 21 patients aged 19 years or younger (at date of transplant) with PTLD following SOT or HSCT having adequate tumor samples available (n = 29). Using immunohistochemistry, we evaluated PD‐L1/PD1 expression on both tumor cells and cells of the microenvironment in all samples. Availability of consecutively matched tumor samples during 6 of 21 patients' disease courses also allowed an intra‐individual assessment of PD‐L1/PD1 expression. We observed lower PD‐L1 and higher PD1 expression in non‐destructive lesions, and higher PD‐L1 and lower PD1 expression in polymorphic and, in particular, in monomorphic PTLD, mostly diffuse large B‐cell lymphomas (DLBCL, n = 10/21). The amount of PD‐L1‐ and PD1‐positive cells changed in the opposite way in sequential biopsies of the same individual correlating well with the PTLD category. This is the first comprehensive pediatric study assessing PD‐L1 and PD1 expression on tumor cells and in the microenvironment of PTLD including not only monomorphic, but also non‐destructive early lesions. PD‐L1 expression of the tumor cells inversely correlated with PD1 expression in surrounding tissues, with the highest expression in DLBCL. Since PTLD can be therapeutically challenging, our results indicate a potential efficacy of checkpoint inhibitors if standard immune‐ and/or chemotherapy fail or are impossible. We therefore recommend routine staining of PD‐L1 and PD1 in all PTLD categories. Abstract : The inverse correlation of PD‐L1 and PD1 expression in all categories of PTLD with the highest levels of PD‐L1 and lowest levels of PD1 expression in monomorphic PTLD suggests the following: existence of immune modulatory effects of B‐cell tumor cells, additional routine PD‐L1 and PD1 staining in all PTLD categories, and PD‐L1 as a potential therapeutic target for checkpoint inhibitors in case of failure or impossibility of standard immune‐ and chemotherapy in these usually multi‐moribund pediatric transplant patients with PTLD.